Bulgakov Case: the Can(n)on and the Context (City: History, Culture, Society, 2025)
«The Bulgakov case» appears to be perfectly tailored for analyzing the changes in Ukrainian cities' symbolic landscape and public spaces today. This paper explores how decolonization affects current practices and «conceptualizations» of heritagization, de-heritagization, and re-heritagization (Harrison, 2013), and how these processes are approached on both institutional and popular levels. Starting with an analysis of how imperial imagery emerged and shaped the «Kyiv myth» and the overall image of Kyiv, to which Bulgakov contributed and which he zealously retransmitted, the paper will examine the role the «Bulgakov myth» still plays in heritagization as decolonization processes gain momentum. Finally, we will analyze possible ways of working with different groups of objects — monuments, and buildings — as part of the heritagization process, i.e., constructing a body of historical and cultural memory in contemporary Ukraine.
Keywords: decolonisation; historical/cultural heritage; «Kyiv myth»; symbolic landscape; imperial narrative; matrix of colonial imagination; nostalgia; olonial subject